Pengaruh Anteseden Manajemen Rantai Pasok Terhadap Kinerja Distributor Di Pulau Batam Yang Dimediasi Oleh Keunggulan Kompetitif - Septriana, Septriana; Zai, Immanuel (MBIA, 2023)
This research aims to analyze the influence of Supply Chain Management antecedents on Distributor Performance mediated by Competitive Advantage on Batam Island. This research uses quantitative methods, and the sampling technique is non-random (purposive sampling). The population includes manufacturing companies, suppliers and distributors on the island of Batam. This research targets 250 respondents, with sample criteria being distributors, procurement, purchasing, general suppliers, agents, retailers and resellers. The total number of questionnaires was 250, distributed online via Google Forms—data processing and analysis through the SMART-PLS application and Structure Equation Modeling. The results of this research state that Supply Chain Management consisting of Strategic Supplier Partnership, Customer Relationship Management, and Level of Information Sharing has an insignificant effect on Distributor Performance but has a significant positive effect on Competitive Advantage. Competitive advantage has a significant positive effect on Distributor Performance, and Competitive advantage has a significant positive effect on the relationship between Strategic Supplier Partnership, Customer Relationship Management and Level of Information Sharing on distributor performance. Keywords: Distributor performance, Strategic Supplier Partnership, Customer Relationship Management, Level Of Information Sharing, Competitive Advantage Abstrak Tujuan penelitian ini adalah menganalisa pengaruh anteseden Manajemen Rantai Pasok terhadap Kinerja Distributor yang dimediasi oleh Keunggulan Kompetitif di Pulau Batam. Penelitian ini menggunakan metode kuantitatif dan teknik pengambilan sampelnya secara tidak acak (purposive sampling). Populasi nya mencakup perusahaan-perusahaan manufaktur, supplier, dan distributor di pulau Batam. Penelitian ini menargetkan 250 responden dengan kriteria sampelnya adalah distributor, procurement, purchasing, general supplier, agen, retailer, dan pengecer. Jumlah keseluruhan kuisioner sebanyak 250 disebarkan secara online melalui Google Form. Pengolahan data dan analisis data melalui aplikasi SMART-PLS dan menggunakan Structure Equation Modelling. Hasil penelitian ini menyatakan bahwa Manajemen Rantai Pasok yang terdiri dari Strategic Supplier Partnership, Customer Relationship Management, dan Level of Information Sharing berpengaruh tidak signifikan terhadap Distributor Performance namun berpengaruh signifikan positif terhadap Competitive advantage. Competitive advantage berpengaruh signifikan positif terhadap Distributor Performance dan juga Competitive advantage berpengaruh signifikan positif dalam hubungan Strategic Supplier Partnership, Customer Relationship Management, dan Level of Information Sharing terhadap distributor performance. Kata kunci: Kinerja Distributor, Kemitraan Pemasok Strategis, Pengelolaan Hubungan Pelanggan, Tingkat Pembagian Informasi, Keunggulan kompetitif.